Work disability and health-related quality of life in males and females with psoriatic arthritis. Issue 5 (29th May 2008) - Wallenius, M; Skomsvoll, J F; Koldingsnes, W; Rødevand, E; Mikkelsen, K; Kaufmann, C; Kvien, T K
Abstract : Objectives: To compare health status, demographic variables and work disability (WD) between males and females with psoriatic arthritis (PsA) in the 18–45 age group, and further to compare health status between those with and without WD for each gender and to identify variables associated with WD. Methods: A cross-sectional study was carried out of patients with PsA with peripheral arthritis at the time at which they started disease-modifying antirheumatic drug therapy (DMARD) and/or biological treatment. Patients receiving a permanent national WD pension corresponding to ⩾50% were defined as work disabled. Gender differences were examined with regard to health status, demographic variables and WD. Mann–Whitney U test and Pearson χ 2 were applied for group comparisons between males and females and work disabled versus not work disabled for each gender. Multiple logistic regression analyses with adjustments for duration of education, disease duration, age, erosive disease, disability score (Modified Health Assessment Questionnaire; MHAQ), the short form-36 (SF-36) mental health score, and gender were used to identify variables associated with WD. Results: Out of 271 (102 females) patients, the number (%) of work-disabled females/males was 33 (32.7%)/29 (17.4%) (p = 0.004). Work-disabled patients had generally worse health status than non-work-disabled patients, and these differences were generally more pronounced in males than in females. In the multiple logistic regression model, low educational level, increasing disability score (MHAQ), presence of erosive disease, female gender and disease duration were independently associated with WD. Conclusions: WD in patients with PsA below 45 years of age was independently associated with educational level, disability score, erosive disease, female gender and disease duration.